Prevalence of oral submucous fibrosis in relation to habits among high school children of Kanpur City: A cross-sectional study - Rahul Srivastava; Sartaj S Wazir; Devina Pradhan; Lokesh Sharma; Rohit Kumar; Priyanka Kumari (Wolters Kluwer Medknow Publications, 2021)
Background: Oral submucous fibrosis (OSMF) is a chronic insidious disease that affects oral cavity, may also involve pharynx or esophagus, and may be associated with vesicle formation. The present study aimed to determine prevalence of oral submucous fibrosis among school children in Kanpur city through cross-sectional study and its association with various type of quid and areca nut chewing habit. Materials and Methods: In different urban and rural educational areas of the Kanpur district of Uttar Pradesh, a school-based cross-sectional study was carried out. Data on consumption of areca nut were obtained by a self-administered questionnaire based on demographic characteristics, areca nut use, daily frequency of areca nut chewing, other ingredients mixed with nut, tobacco use (smoking and/or chewing), age of initiation of nut chewing, reasons for use, social influence factors, and risk perceptions. All oral examinations were done by specialist examiners who were familiar with oral mucosal lesions in the local population. Results: The results from this study shows that the areca nut chewing habit is significant among school children of rural areas as compare to urban areas in Kanpur district. No female subject was found to be suffering from OSMF in both the urban as well as rural areas however 27 (3.41%) male subjects were found to be suffering from OSMF. Conclusion: In order to spread awareness through educational programs, newspapers, and mass media in neighborhoods and classrooms, steps should be taken at the public health level.